Automatic motor speed reference generators for cruise and lateral control of electric vehicles with in-wheel motors. (October 2018) - Pomponi, C.; Scalzi, S.; Pasquale, L.; Verrelli, C.M.; Marino, R.
Abstract: Motor speed reference generators have been recently presented in the literature for the cruise control of electric vehicles powered by centralized electric motors. Steady-state operation at a safe tire longitudinal slip is guaranteed to be achieved in the presence of uncertain external conditions. In this paper, a generalization of the aforementioned result to electric vehicles that make use of two in-wheel motors and are required to perform a bend manoeuvre is provided. A new cruise and lateral control is presented. The two in-wheel rear motors provide propulsion, while being capable of acting as a rear differential. The key point relies on the definition of suitable references for the two motor speeds, so that motor speed control algorithms can be directly inherited from the electric machine control literature, while intrinsically robust motor speed control loops can be additionally incorporated. Both CarSim simulations and experiments are included to illustrate the practical effectiveness of the proposed approach.